1998
DOI: 10.1007/s004320050155
|View full text |Cite
|
Sign up to set email alerts
|

Survival in patients with primary soft-tissue sarcomas treated within 6 years

Abstract: Since 1988, treatment strategies for our sarcoma patients have been determined by the same team and operations performed by one surgeon. The aim of this study was to analyse prognostic data on local recurrence and survival of 101 consecutive patients who presented in our institution with the primary tumour manifestation. After a median follow-up of 35 months, the local recurrence rate was 13.5%, the mean survival time was 68 months and the 5-year survival rate was 83%. Besides positive lymph nodes (only 3 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
2
2
0
1
Order By: Relevance
“…Local recurrence has previously been found to be related to patient survival [35], but our analysis did not find a significant influence of local recurrence on patient prognosis, underlining other recently published data about sSTS and STS in general [35, 36]. In a recent report from our institution we reported that local recurrences of soft tissue sarcoma can be resected in almost all cases, with no significant adverse effect on survival [19].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Local recurrence has previously been found to be related to patient survival [35], but our analysis did not find a significant influence of local recurrence on patient prognosis, underlining other recently published data about sSTS and STS in general [35, 36]. In a recent report from our institution we reported that local recurrences of soft tissue sarcoma can be resected in almost all cases, with no significant adverse effect on survival [19].…”
Section: Discussionsupporting
confidence: 68%
“…In the present series, T2 tumors were negatively associated with freedom from local recurrence. Our results accentuate the need for a radical surgical approach to the primary tumor; for all subcutaneous tumors a radical resection achieving three-dimensional tumor-free resection margins may be associated with improved freedom of local recurrence [19]. The prognostic influence of initial optimal resection on local resection in spite of initial re-excision was demonstrated in a recent study that supports the demand for treatment of STS in specialized centers [20].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The most important prognostic factor identified so far is the quality of surgical treatment at initial diagnosis [2]. Meanwhile, new prognostic factors are sought in order to specifically assess the importance of an adjuvant or palliative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Die adjuvante postoperative Strahlentherapie hat allerdings keinen Einfluss auf das Gesamtüberleben [23,24]. Dieses bestätigen auch Peiper et al bei subfaszialen Weichteilsarkomen größer als 5 cm (T2b) [29]. Heute wird die Kombination von radikaler R0-Resektion und postoperativer Strahlentherapie als Standardvorgehen bei subfaszialen sowie T2 Weichteilsarkomen angesehen [30].…”
Section: Adjuvante Strahlentherapie (Postoperativ Bei Negativen Oder unclassified